2011
DOI: 10.1128/aac.01569-10
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Activities of Anidulafungin and Other Antifungal Agents against Biofilms Formed by Clinical Isolates of Different Candida and Aspergillus Species

Abstract: We tested the activities of anidulafungin and other antifungal agents against clinical isolates of different fungal species. For Candida species, high sessile MIC 90 s (SMIC 90 s) were obtained for fluconazole, voriconazole, and amphotericin B, whereas the anidulafungin SMIC 90 s were very low, as were those for caspofungin. Comparatively, for Aspergillus species, higher SMIC 90 values were obtained not only for amphotericin B and voriconazole but also for the echinocandins.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
49
1
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 68 publications
(56 citation statements)
references
References 27 publications
5
49
1
1
Order By: Relevance
“…Biofilms formed by C. albicans cells usually increase resistance to commonly used antifungal drugs, such as azoles and amphotericin B (Walker et al ., 2010; Fiori et al ., 2011). It is important to develop new antifungal drugs that efficiently control biofilm formation.…”
Section: Discussionmentioning
confidence: 99%
“…Biofilms formed by C. albicans cells usually increase resistance to commonly used antifungal drugs, such as azoles and amphotericin B (Walker et al ., 2010; Fiori et al ., 2011). It is important to develop new antifungal drugs that efficiently control biofilm formation.…”
Section: Discussionmentioning
confidence: 99%
“…All the isolates were retrieved from their frozen glycerol stocks and were streaked on fresh Sabouraud dextrose agar (Kima, Padua, Italy) plates, until good sporulation was achieved following incubation at 37°C. For all experiments, conidial suspensions in RPMI 1640 medium (Sigma-Aldrich, Milan, Italy) were obtained as described elsewhere (12,28) and used to prepare the inocula (see below).…”
Section: Methodsmentioning
confidence: 99%
“…This growth phenotype, which complies with the definition of a biofilm (10), may help A. fumigatus to colonize the host substratum and to resist phagocytic and antimicrobial attacks, mimicking the typical Candida albicans or bacterial biofilm (8,11). Recent observations have consistently shown that all antifungal drugs are significantly less effective when A. fumigatus is grown as a biofilm than when it is grown in the planktonic state (4,7,9,12,13), presumably as a reflection of multiple resistance mechanisms, including the ECM, which would prevent drug diffusion by acting as a physical barrier (14). This could contribute to the overall mortality with invasive aspergillosis, which remains high, despite the use of newer broad-spectrum antifungal agents and diagnostic adjuncts (15).…”
mentioning
confidence: 99%
“…Echinocandins are fungicidal for Candida planktonic cells (nonattached cells) and exhibit activity against mature biofilms of several Candida species (13)(14)(15)(16)(17). There have been several studies on the efficacy of echinocandins against Candida biofilms (18)(19)(20)(21), the occurrence of the paradoxical effect observed with this class of antifungals (22,23), and the role of echinocandin lock solutions in the management of candidiasis related to implanted devices (24); however, there are no comprehensive reports that have compared the in vitro activities of the three echinocandins against biofilms formed by different non-albicans Candida spp. The aim of this study was to determine the antifungal activities of anidulafungin (ANID), caspofungin (CAS), and micafungin (MFG) against planktonic cells as well as biofilms formed by non-C. albicans Candida bloodstream isolates, such as C. parapsi-losis, C. krusei, C. lusitaniae, and C. guilliermondii, in comparison to those of C. albicans.…”
mentioning
confidence: 99%